2005
DOI: 10.1088/0953-8984/17/21/007
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of defects in amorphous silica: new insights from embedded cluster calculations

Abstract: We briefly review some of the approaches which have been used to study the distributions of defect properties in amorphous silica and focus mainly on the implementation of the embedded cluster method. We illustrate some of the results obtained using this method and discuss the remaining problems using the example of oxygen vacancy defects in amorphous SiO 2 . The neutral vacancies are characterized by a wide distribution of formation energies and structural parameters. Our modelling predicts the two major stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 96 publications
(200 reference statements)
10
62
0
Order By: Relevance
“…agreement with electron paramagnetic resonance (EPR) experiments [3,4]. However, significant challenges remain; the high concentration of E' centers observed experimentally in stoichiometric a-SiO 2 , see for example…”
supporting
confidence: 57%
See 2 more Smart Citations
“…agreement with electron paramagnetic resonance (EPR) experiments [3,4]. However, significant challenges remain; the high concentration of E' centers observed experimentally in stoichiometric a-SiO 2 , see for example…”
supporting
confidence: 57%
“…Theoretical calculations have shown that an EPR-active center occurs when one of the silicon atoms retreats from the oxygen vacant site and becomes tetrahedrally coordinated with another oxygen atom in the amorphous network, known as the puckered configuration [3]. The resulting structure leaves an unpaired electron spin localized on a single silicon sp 3 hybrid orbital and has spectroscopic signals consistent with the EPR experiments on the E' γ center.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Figure 1b shows the puckered structure in which one of the two Si atoms that originally bond to the missing O atom puckers back and bonds with an O atom, forming a 3-fold coordinated O (solid arrow), while the other Si atom retains a Si-dangling bond (dashed arrow). This structure plays a key role in hole-trapping-related phenomena in SiO 2 [10,[20][21][22]. Figure 1c is the new configuration of oxygen vacancy.…”
mentioning
confidence: 96%
“…In Figure 1 we show the two known structures of an oxygen vacancy V O [19][20][21][22] along with the new structure that accounts for the experimental data. Figure 1a shows the dimer structure of V O that is formed when one O atom (marked by solid arrow) is removed.…”
mentioning
confidence: 99%